2007
DOI: 10.1308/003588407x202074
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Emergency Ambulance Service (HEAS) Transfer: An Analysis of Trauma Patient Case-Mix, Injury Severity and Outcome

Abstract: Ann R Coll Surg Engl 2007; 89: [513][514][515][516] 513 Helicopters were used very successfully for the transfer of wounded soldiers from the battlefields in the Korean and Vietnam wars and this model of patient transfer was then put into use in a civilian setting, initially in the US. In 1987, the first helicopter-based ambulance service in the UK was introduced in the Greater London region. 1Although this service carries an emergency physician as crew, it is unique in that respect. All other 15 dedicated HEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…[15][16][17][18][19][20][21] A study from a single institution in Great Britain of 156 injured patients with a mean ISS of 12 transported by helicopter reported that 45 patients were discharged within 24 hours. 22 This ISS was much lower than the mean ISS for the patients transported by helicopter in the present study and was more comparable to that of the patients transported by ground ambulance. A large meta-analysis of 22 studies with 37 350 patients by Bledsoe and colleagues 23 noted that 60% of patients had an ISS of 15 or less and that 24% were discharged within 24 hours.…”
Section: Discussionsupporting
confidence: 39%
“…[15][16][17][18][19][20][21] A study from a single institution in Great Britain of 156 injured patients with a mean ISS of 12 transported by helicopter reported that 45 patients were discharged within 24 hours. 22 This ISS was much lower than the mean ISS for the patients transported by helicopter in the present study and was more comparable to that of the patients transported by ground ambulance. A large meta-analysis of 22 studies with 37 350 patients by Bledsoe and colleagues 23 noted that 60% of patients had an ISS of 15 or less and that 24% were discharged within 24 hours.…”
Section: Discussionsupporting
confidence: 39%
“…A study by Melton et al, involving three services of aeromedical rescue in the England countryside, showed an average ISS of 12 among their patients, 41% of them having been discharged directly from the emergency department (mean ISS of 1 to the latter group) 28 . Shatney et al conducted a retrospective analysis of 947 patients taken by AR to a trauma center in California over a period of ten years and found an average ISS of 8.9, only 148 of them (15.6% ) having ISS > 15 29 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…A HEMS operation is usually only faster over distances >45 km, in poor road conditions and when traffic conditions are congested. [12] The majority of the patients transported were adult males. This appears to be in line with international trends, although many studies have only included patients aged >15 years.…”
Section: Discussionmentioning
confidence: 99%